MRSA Spinal Epidural Abscess as a Neurosurgical and Infectious Disease Emergency with Unresolved Antimicrobial Solution - James Ebot; W. D. Freeman; Robert Wharen; Mark Anthony Diaz; Claudia Libertin (Case Reports in Infectious Diseases)
Spinal epidural abscess caused by MRSA, a life-threatening organism resistant to methicillin and other antibiotics, is a rare but important infectious pathology due to its potential damage to the spinal cord. We present the case of a 74-year-old man who hematogenously seeded his entire epidural spinal canal from C1 to sacrum with MRSA bacteria and remained infected even after maximal treatment with vancomycin and daptomycin. Ceftaroline, a new 5th generation antibiotic with recently described clearance of widespread MRSA infection in epidural complex spine infections, was added to vancomycin as dual therapy for his MRSA infection. A 74-year-old diabetic man with prior right total knee arthroplasty and MRSA infection presented with persistent bacteremia and sepsis. He was transferred to our academic center after diagnosis of entire spine epidural abscesses from C1 to sacral levels with midthoracic MRI T2 hyperintensities of the vertebral bodies and disc concerning for osteomyelitis and discitis. Despite surgery and IV vancomycin with MIC of 1, suggesting extreme susceptibility, the patient’s blood cultures remained persistently bacteremic at day 5 of treatment. After 48 hours of dual antibiotic therapy with vancomycin and ceftaroline, his blood cultures came back showing no growth. The patient’s outcome was unfavorable due to the advanced nature of his infection and multiple comorbidities, but his negative blood cultures after the addition of ceftaroline to his regime require further investigation into this dual therapy. Randomized controlled trials of 5th generation or combinatorial antibiotics should be considered for this disease.